FENOMENA OTOT POSITIF PADA KELAINAN NEUROMUSKULAR - Angelita, Michelle Cancera; Indrawati, Luh Ari; Hakim, Manfaluthy; Octaviana, Fitri; Budikayanti, Astri; Safri, Ahmad Yanuar; Wiratman, Winnugroho; Fadli, Nurul; Harsono, Adrian Ridski (PERDOSNI, 2024)
Positive muscle phenomena arise due to various forms of spontaneous muscle hyperactivity originating from motor neurons or the muscle itself. The presence of this phenomenon can constringe the possible diagnosis to be more specific, so if presence it is necessary to be identified in patients with potential neuromuscular disease. However, the presence of positive muscle phenomena is often overlooked. This gap in our knowledge regarding definitions, clinical findings, electrodiagnostic findings, and pathophysiological mechanisms hampers effective diagnosis and treatment. In this article, we review the clinical characteristics approach to diagnosis of various positive muscle phenomena originating from the lower motor neuron (LMN) and muscle, including tetany, cramps, fasciculations, myokymia, neuromyotonia, rippling muscle, percussion induced rapid contractions (PIRCs), myoedema, and contractures. Keywords: fasciculation, muscle phenomena, hyperactivity, myotonia, rippling muscle